Prospect theory and SERVQUAL - Burböck, Birgit (Management, 2014)
The aim of this paper is to make a scientific contribution for a better understanding of the relationship between the Prospect Theory and servqual. The first objective is to analyse whether the servqual scale is an appropriate scale to quantify service quality and customer satisfaction of automobile-insurances. The second objective is to discuss the relationship between service quality and customer satisfaction. With the prospect theory, the relationship is explained and described. Only a negative asymmetric relationship between service quality and customer satisfaction can be explained by the prospect theory. The proposed diminishing sensitivity lacks sufficient significant empirical evidence.
Keywords: kupci; kvaliteta; storitve; uporabniki; zadovoljstvo